The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4137/ebo.s36436
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics, Metatranscriptomics, and Metabolomics Approaches for Microbiome Analysis

Abstract: Microbiomes are ubiquitous and are found in the ocean, the soil, and in/on other living organisms. Changes in the microbiome can impact the health of the environmental niche in which they reside. In order to learn more about these communities, different approaches based on data from multiple omics have been pursued. Metagenomics produces a taxonomical profile of the sample, metatranscriptomics helps us to obtain a functional profile, and metabolomics completes the picture by determining which byproducts are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
217
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(236 citation statements)
references
References 167 publications
(187 reference statements)
0
217
0
4
Order By: Relevance
“…It is complemented by metatranscriptomics, which defines the collection of genes expressed by a particular microbial community, and by metaproteomics and metabolomics, which define the proteins and metabolites (such as short and medium chain fatty acids) collectively produced (or metabolized) by the microorganisms (table 1). 2122 Whole genome shotgun sequencing is used to infer the functional or enzymatic capabilities of the identified microorganisms 20…”
Section: Introduction Definitions and Nomenclaturementioning
confidence: 99%
“…It is complemented by metatranscriptomics, which defines the collection of genes expressed by a particular microbial community, and by metaproteomics and metabolomics, which define the proteins and metabolites (such as short and medium chain fatty acids) collectively produced (or metabolized) by the microorganisms (table 1). 2122 Whole genome shotgun sequencing is used to infer the functional or enzymatic capabilities of the identified microorganisms 20…”
Section: Introduction Definitions and Nomenclaturementioning
confidence: 99%
“…We share an optimistic view on the basis of the metatranscriptomic, metaproteomic and metabonomic studies being reported (Lim et al, 2013; Aguiar-Pulido et al, 2016; Yu et al, 2016). The NIH-sponsored Human Microbiome Project has been established to comprehensively characterize human microbiota from multiple body sites and analyze their impact in human health and disease (Peterson et al, 2009; Proctor, 2016).…”
Section: “Which Entities Are Active?”mentioning
confidence: 97%
“…Объединение подходов метагеномики, метатранскриптомики и метаметаболомики даёт более полное представление о микробиоме [9]. Использование вместе ко-ассоциативных и метаболических сетей позволит глубже понимать скрытые механизмы, обеспечивающие стабильность и динамику мик-робных сообществ [16].…”
Section: метаметаболомunclassified